Dietary Reference Intakes: Applications in Dietary Assessment - Institute of Medicine (The National Academies Press, 2000)
Since 1994 the Institute of Medicine's Food and Nutrition Board has been involved in developing an expanded approach to developing dietary reference standards. This approach, the Dietary Reference Intakes (DRIs), provides a set of four nutrient-based reference values designed to replace the Recommended Dietary Allowances (RDAs) in the United States and the Recommended Nutrient Intakes (RNIs) in Canada. These reference values include Estimated Average Requirement (EAR), Recommended Dietary Allowance (RDA), Adequate Intake (AI), and Tolerable Upper Intake Level (UL). To date, several volumes in this series have been published. This new book, Applications in Dietary Assessment, provides guidance to nutrition and health research professionals on the application of the new DRIs. It represents both a "how to" manual and a "why" manual. Specific examples of both appropriate and inappropriate uses of the DRIs in assessing nutrient adequacy of groups and of individuals are provided, along with detailed statistical approaches for the methods described. In addition, a clear distinction is made between assessing individuals and assessing groups as the approaches used are quite different. Applications in Dietary Assessment will be an essential companion to any-or all-of the DRI volumes.
Keywords: Food and Nutrition

Dietary Reference Intakes for Water, Potassium, Sodium, Chloride, and Sulfate - Institute of Medicine (The National Academies Press, 2005)
Dietary Reference Intakes for Water, Potassium, Sodium, Chloride, and Sulfate The Dietary Reference Intakes (DRIs) are quantitative estimates of nutrient intakes to be used for planning and assessing diets for healthy people. This new report, the sixth in a series of reports presenting dietary reference values for the intakes of nutrients by Americans and Canadians, establishes nutrient recommendations on water, potassium, and salt for health maintenance and the reduction of chronic disease risk. Dietary Reference Intakes for Water, Potassium, Sodium, Chloride, and Sulfate discusses in detail the role of water, potassium, salt, chloride, and sulfate in human physiology and health. The major findings in this book include the establishment of Adequate Intakes for total water (drinking water, beverages, and food), potassium, sodium, and chloride and the establishment of Tolerable Upper Intake levels for sodium and chloride. The book makes research recommendations for information needed to advance the understanding of human requirements for water and electrolytes, as well as adverse effects associated with the intake of excessive amounts of water, sodium, chloride, potassium, and sulfate. This book will be an invaluable reference for nutritionists, nutrition researchers, and food manufacturers.
Keywords: Food and Nutrition

Dietary Reference Intakes for Sodium and Potassium - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
As essential nutrients, sodium and potassium contribute to the fundamentals of physiology and pathology of human health and disease. In clinical settings, these are two important blood electrolytes, are frequently measured and influence care decisions. Yet, blood electrolyte concentrations are usually not influenced by dietary intake, as kidney and hormone systems carefully regulate blood values.
Keywords: Food and Nutrition